Silencing of A-kinase anchor protein 4 inhibits the metastasis and growth of non-small cell lung cancer. Issue 3 (1st March 2022) - Zhang, Bo; Hu, Quanteng; Zhang, Jian; Jin, Zixian; Ruan, Yuhang; Xia, Lilong; Wang, Chunguo
ABSTRACT: Non-small cell lung cancer (NSCLC) is one of the most malignant tumors. The treatment of advanced NSCLC can be challenging due to drug resistance. The discovery of novel cancer-testis antigens to develop new strategies for advanced metastatic NSCLC is required. AKAP4 is an oncogene discovered in some malignant tumors, and its molecular function of AKAP4 in NSCLC is unknown. This study aimed to explore the potential function of AKAP4 in the development and progression of NSCLC. AKAP-4 was found to be significantly upregulated in both clinical NSCLC tissues and NSCLC cell lines. Cell viability and migration were suppressed, apoptosis was induced, and tube formation was inhibited by the knockdown of AKAP-4, accompanied by the downregulation of VEGF, N-cadherin, EphA2, and MMP-2, and upregulation of c-AMP, PKA, and E-cadherin. In vivo xenograft experiments revealed that tumor growth was inhibited by the knockdown of AKAP4, accompanied by the activation of c-AMP/PKA signaling and inhibition of epithelial-mesenchymal transition progression. Our results show that AKAP4 might be an important target for treating NSCLC because of its function in promoting the migration and proliferation of NSCLC cells.